Default statistics Private and sub-sovereign lending 2001-2019 - European Investment Bank (European Investment Bank, 2021)
To address the need for greater volumes of private investment tackling sustainable development goals in the most isolated regions, the Global Emerging Markets Risk Database Consortium (GEMs) issued its first public report on credit default statistics for private and sub-sovereign lending. Established by the European Investment Bank and the International Finance Corporation, GEMs is a network of 25 multilateral development banks and development finance institutions. GEMs pools anonymised credit information with a focus on emerging markets and developing countries where data are scarce and finance is most needed. Since 2009, the GEMs members have collected and shared credit risk data internally. Members have now decided to make this knowledge public. More information on the GEMs consortium can be found at www.gemsriskdatabase.org